Very late recurrence of Wilms' tumor at the uterus and concurrent BRCA2 risk reduction: A case report - Jill Alldredge; Cariza Mercurio; Michael Berman (Elsevier, 2019)
This case report describes a young woman who, after a 24-year disease free interval from her advanced childhood Wilms' tumor, developed a large symptomatic pelvic mass contiguous with the uterus. This proved to be a surgically unresectable recurrent Wilms' tumor and she had an excellent response to systemic chemotherapy. A second attempt at hysterectomy proved unsuccessful, however she was able to undergo an ovarian cancer risk-reducing surgery for a pathogenic BRCA2 mutation which was detected during the care of her cancer recurrence. Keywords: Late uterine, Wilms' tumor recurrence